Inappropriate prescribing of antibiotics to the patients with acute bronchitis - Petrovic, Marijana S.; Antonic, Roland A.; Bagi, Bojan I.; Ilic, Irena M.; Kocovic, Aleksandar Goran; Milosavljevic, Milos N.; Nedovic, Nikola M.; Pejcic, Ana V.; Vapljanin, Minela Z.; Sabanovic, Admir M.; Jankovic, Slobodan M. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Inappropriate prescribing of antibiotics to the patients with acute bronchitis is frequent event in clinical practice with potentially serious consequences, although majority of treatment guidelines do not recommend it. The aim of this study was to reveal risk factors associated with inappropriate prescribing of antibiotics to the patients with acute bronchitis in primary healthcare. Methods. This case/control study included the adult patients with acute bronchitis during the initial encounter with a general practitioner. Prescription of an antibiotic was an event that defined the case, and patients without prescribed antibiotic served as controls. Results. Antibiotics (mostly macrolides and beta-lactams) were prescribed to the majority of patients with diagnosis of acute bronchitis (78.5%). A significant association was found between antibiotic prescription rates and patient age, whether an attending physician is a specialist or not and the average number of patients a physician sees per day [ORadjustedwas 1.029 (1.007–1.052), 0.347 (0.147–0.818) and 0.957 (0.923–0.992), respectively]. Conclusion. When there is primary care encounter with patients suffering from acute bronchitis, older patients are more likely to receive inappropriate antibiotic prescription, especially if their physician is without specialist training and has less patient encounters in his/her office daily.